Pantallas y retóricas. Interpenetraciones, hibridaciones y recomposiciones en las estéticas actuales de lo audiovisual (Segunda parte) - Proyecto - Tassara, Mabel (2015)
This project is proposed as a continuation of the research conducted in 2013-2014. The approach of rhetoric forms currently present in audiovisual displays -main objective of the previous project- was implemented in relation to different internal lines of study, logical diversification in the light of the many fields in which the operations connected with discursive interpenetration and interaction devices appear. These lines of research have highlighted a huge expressive richness, at once highly diversified, where we can find constant reorganizations that concern historical parameters of the specific languages. This phenomena implies permanent collision of the limits of the historic allocations, including the recent ones; an operation that ultimately leads to modification, in some ways, of modes of speech, both in known fields and in newly created spaces. Modes of speech that force a reconsideration of traditional declarative schemes, outlining in some cases relational constructs that are not easy to associate with existing traditions. This complex situation requires , for the fulfillment of the initial aims, even with the focus on circumscribed spaces and the exploration purposes with which we have been working, a deepening of the investigations and analyzes performed in the first stage.